Morphine treatment enhances glutamatergic input onto neurons of the nucleus accumbens via both disinhibitory and stimulating effect. (22nd August 2016) - Yuan, Kejing; Sheng, Huan; Song, Jiaojiao; Yang, Li; Cui, Dongyang; Ma, Qianqian; Zhang, Wen; Lai, Bin; Chen, Ming; Zheng, Ping
Abstract: Drug addiction is a chronic brain disorder characterized by the compulsive repeated use of drugs. The reinforcing effect of repeated use of drugs on reward plays an important role in morphine‐induced addictive behaviors. The nucleus accumbens (NAc) is an important site where morphine treatment produces its reinforcing effect on reward. However, how morphine treatment produces its reinforcing effect on reward in the NAc remains to be clarified. In the present study, we studied the influence of morphine treatment on the effects of DA and observed whether morphine treatment could directly change glutamatergic synaptic transmission in the NAc. We also explored the functional significance of morphine‐induced potentiation of glutamatergic synaptic transmission in the NAc at behavioral level. Our results show that (1) morphine treatment removes the inhibitory effect of DA on glutamatergic input onto NAc neurons; (2) morphine treatment potentiates glutamatergic input onto NAc neurons, especially the one from the basolateral amygdala (BLA) to the NAc; (3) blockade of glutamatergic synaptic transmission in the NAc or ablation of projection neurons from BLA to NAc significantly decreases morphine treatment‐induced increase in locomotor activity. These results suggest that morphine treatment enhances glutamatergic input onto neurons of the NAc via both disinhibitory and stimulating effect and therefore increases locomotor activity. Abstract : The NAc is an important site where morphine treatment produces its reinforcing effect on reward. We found that morphine treatment removes the inhibitory effect of DA on glutamatergic input onto NAc and potentiates glutamatergic input from BLA to NAc. Blockade of glutamatergic transmission in NAc or ablation of projection from BLA to NAc decreases morphine treatment‐induced increase in locomotor activity.